Efficient near-infrared emission based on donor-acceptor molecular architecture: The role of ancillary acceptor of cyanophenyl. (February 2018) - Tang, Xiaohui; Li, Xiang-Long; Liu, Haichao; Gao, Yu; Shen, Yue; Zhang, Shitong; Lu, Ping; Yang, Bing; Su, Shi-Jian; Ma, Yuguang
Abstract: Herein, a new near-infrared (NIR) material, 4-(9-(4-(diphenylamino)phenyl)naphtho[2, 3- c ][1, 2, 5]thiadiazol-4-yl)benzonitrile (TPA-NZC), was designed and synthesized with the incorporation of an ancillary acceptor (cyanophenyl) into the donor-acceptor (D-A) molecular backbone of a red emitter TPA-NZP (4, 9-diphenylnaphtho[2, 3- c ][1, 2, 5]thiadiazole). Compared with TPA-NZP, TPA-NZC exhibits an NIR emission ( λ max  = 710 nm) with a large redshift, as well as a maintained photoluminescence efficiency (ηPL ) of 17% in film. Moreover, the non-doped OLED based on TPA-NZC emitter exhibits an excellent NIR emission at 702 nm with a maximum EQE of 1.2%, while the doped device achieves a deep-red emission at 656 nm with a maximum EQE of 3.2%. This work further verifies the reliability of "hot exciton" and hybridized local and charge-transfer state (HLCT) mechanism, as well as provides a strategy to design a narrow bandgap light-emitting material by introducing cyanophenyl as an ancillary acceptor in D-A systems. Graphical abstract: Highlights: Cyanophenyl as an ancillary acceptor is attachedto Naphtho[2, 3-c][1, 2, 5]thiadiazole for a highly efficient NIR material. Experimental and theoretical results demonstrate the "hot exciton" and HLCT characteristic of TPA-NZC molecule. TPA-NZC exhibits a NIR emission at λ max  = 710 nm with a high PL efficiency of ηPL  = 17% in evaporated film. The non-doped device based on TPA-NZC as emitter exhibits a NIR emission at 702 nm with a maximum EQE of 1.2%.